Profitabilitas Perusahaan Sektor Consumer Non-cyclical: Pengaruh Leverage, Ukuran Perusahaan, dan Likuiditas - Kesara, Rinaldi; Zahro, Nafi’ Inayati; Susanti, Diah Ayu (AKTSAR: Jurnal Akuntansi Syariah, 2023)
Profitability is the most important element in a company because the profit or profits generated can determine the level of investor confidence in investing. The aim of this research is to examine the effect of leverage, company size and liquidity on profitability levels. This research is quantitative research with a population of Consumer Non-cyclical companies listed on the IDX for the 2017-2022 period. Sampling used a purposive sampling technique with a total of nine companies and obtained 514 research data. Data analysis uses multiple linear regression analysis techniques for panel data with Eviews 9. The results of this research show that leverage and liquidity have a negative effect on profitability. Meanwhile, company size has no effect on profitability.